2022
DOI: 10.5005/ijcdas-52-4-213
|View full text |Cite
|
Sign up to set email alerts
|

Spirometry and Diffusion Studies in Patients with Type-2 Diabetes Mellitus and Their Association with Microvascular Complications

Abstract: Background. Diabetes is a systemic disease with-well known complications involving eyes, kidneys and nerves. The presence of an extensive pulmonary microvascular circulation and abundant connective tissue raises the possibility that lung may also be a target organ in diabetes. Methods.A total of 45 subjects were included in the study. All patients were evaluated for diabetic microangiopathies: nephropathy (by 24-hour protein excretion), retinopathy (by direct ophthalmoscopy) and neuropathy (by clinical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Hence, in the case of diabetic patients with high BMI, FEV1/SVC had a greater diagnostic value than FEV1/FVC. Similar results were observed in a population-based study in Southern Australia, where BMI, coronary artery disease, and age were found to be significant determinants of ventilatory function [ 7 ]. The effect of BMI on reducing lung function has been well documented [ 20 - 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Hence, in the case of diabetic patients with high BMI, FEV1/SVC had a greater diagnostic value than FEV1/FVC. Similar results were observed in a population-based study in Southern Australia, where BMI, coronary artery disease, and age were found to be significant determinants of ventilatory function [ 7 ]. The effect of BMI on reducing lung function has been well documented [ 20 - 24 ].…”
Section: Discussionsupporting
confidence: 88%
“…The effect of VC of diabetic patients on pulmonary function has been reported by many authors [ 6 , 7 ]. The VC decreases with increasing BMI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation